Rise & Fall of Fetal Heart Rate, the Principle of Fetal Monitoring: Hypoxia Index prevents Cerebral Palsy - Kazuo Maeda; Masaji Utsu (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
As FHR rises by the fetal brain excitation with fetal movement, and FHR falls by the excitation of fetal vagus nerve center with hypoxic stimulation, hypoxic grade is numerically known by the hypoxia index, which is the sum of FHR deceleration duration (min) divided by the lowest FHR (bpm), and multiplied by 100, where all of 6 cerebral palsy cases' hypoxia index were 25 or more, while the hypoxia index of all 16 no cerebral cases were 24 or less, thus, cerebral palsy is prevented, if the hypoxia index is 24 or less in full course of fetal monitoring. It is the first numeric threshold setting to prevent cerebral palsy in 50 years' history of fetal monitoring.